Limbah Cair Industri Kakao Sebagai Bahan Pembuat Nata - Y Yunianta (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
This research was aimed to utilize the liquid waste of cacao industry as raw material for nata production. Research was performed in two steps : the first steps was clarification process using active charcoal in different waste dilllutions and the second step was the production of nata. Result of first step showed that active charcoal concentration and dilution treatment showed their effect of all parameters studied. The best result was obtained by treatment of 5% active charcoal concentration and the dilllution of cacao waste : water in 1:3 ratio. The production of nata in the second step of research was performed using this optimal clarification condition. Data showed that the combination treatment of 4% sucrose concentration and 0,4% of (NH4)2SO4 was elected as the best process that gave the best quality of nata. The best treatment showed product characteristic : 83,87% of fermentation yield; 95,23% of moisture content; 4,22% of fiber content; brightness (L*) of 42,87; 0,01 mm/g.dt of textur and 2,42 cm of nata thickness.